(3GdLGeY GdUZjQ ef MOjK GdHTjQ GdfPjQs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3YHO GdbGOQ GdbQGai GdCRgQi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi HYK Ydi QCS cd eGFI SfI ef jLOO dgPg GdCeI CeQ OjfgG gPG cJGH ChOYJ ajg ef Gdcde GdfHhjI CdhakG hQJHJg Ydi MQha GdeYLe s
(3BNQgG (B:s
(3gPG BNQ GdLGeY GdUZjQ bGd eDdag aQZJ ef JGdjag SfI SHY hJSYeGFg s
(3HgG fXGe GdJYbjHIs
(3fSNI CNQis
(3cJHJ ChGFd GdCMGOjK hGdQehR ajgG HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs